Isoniazid Preventive Therapy in HIV-Infected Pregnant and Postpartum Women. Issue 2 (June 2020) - Gupta, A.; Montepiedra, G.; Aaron, L.; Theron, G.; McCarthy, K.; Bradford, S.; Chipato, T.; Vhembo, T.; Stranix-Chibanda, L.; Onyango-Makumbi, C.; Masheto, G.R.; Violari, A.; et al.
Abstract : ( N Engl J Med . 2019;381:1333–1346) Among persons with human immunodeficiency virus (HIV) infection who reside in low-income and middle-income countries, tuberculosis (TB) is the leading cause of health complications and death. Among women, TB predominantly affects those of reproductive age. When developing during pregnancy or the early postpartum period, TB is associated with adverse maternal, pregnancy, and infant outcomes. While consensus exists for the net benefit of treating TB during pregnancy, safety and efficacy data are lacking regarding isoniazid (INH) preventive therapy in pregnant women who are receiving antiretroviral therapy (ART).